(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Enzymes haven used long in food processing before their discovery as a biological catalyst. Food fermentation was among the early art of food processing and the use of enzymes in fermentation and cheese making started about 6000 BC. The roles of enzymes in food processing and preservation contributed to the development of mankind. They contributed in the areas of baking, cheese making, dairy processing, milling, cereals technology, juice and beverages processing, vegetable processing, oils and fats processing, and wine processing among others. Microorganisms are the earliest and foremost source of enzymes used in food processing, other sources are plant and animal tissues and organs. Advances in science and technology disclosed more potentials of enzymes and biotechnology open doors for commercial production of enzymes with charming properties. The development of enzyme immobilization techniques allows the reused of enzymes without affecting their properties, structure, or activities. Recent advances in genetic engineering and recombinant DNA technology permit the production of enzymes with exceptional properties. The current trends in the production of Extremozymes will open doors for using enzymes under extreme conditions of temperature, pH, and pressure. In food, processing enzymes can be used as ingredients, processing aid, or as a catalyst for both pre-and post-consumption catalysis. Enzymes improve the quality, shelf life, stability, and sensory properties of foods. They play important roles in food processing by lowering energy consumption, minimizing waste, producing desired products specifically required, and making foods more affordable, palatable, and available